Defining the optimal gradient doped $\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let ≤ =\leqslant \let \ge =\geqslant \let ≥ =\geqslant \def \Pr {Pr}\def \Fr {Fr}\def \Rey {Re}Yb^{3+}$:YAG disk for room and low temperature diode pumped solid-state laser operations. (2nd October 2014) - Chanteloup, J.-C.; Arzakantsyan, M.; Marrazzo, S.
Abstract: We propose a general methodology to define the optimum doping ion volume distribution required for an efficient solid-state laser amplifier. This approach is illustrated in the context of two experimental diode pumped Yb:YAG amplifiers operating at 300 and 160 K. Processing of such tailored gain media is now possible through horizontal direct crystallization.